Evaluation on the impact of environmental management system on the input use of San Miguel Corporation Davao brewery - Gonzales, Arthur M.
Industries are vital components of the economy. Through the years, the industries have both contributed to the development of this country and, unfortunately, to the problem of pollution and environmental degradation. ISO 14001 or the Environmental Management System (EMS) aims to reconcile this dilemma. Amidst unsuccessful management systems, EMS promises to enable the industries reduce their polluting capacity without compromising competitiveness. In the country, San Miguel Davao Brewery is one of those taking the lead in adopting EMS. It is therefore the purpose of this undergraduate thesis entitled 'Evaluation of the Impact of Environmental Management System on the Input Use of San Miguel Corporation Davao Brewery' to conduct a careful analysis regarding the efficiency of the aforementioned system. Using Cobb-Douglas production function as a model, the study quantitatively accounted and regressed the 1997-2001 data obtained from the brewery focusing mainly on the level of input use and the savings obtained by the said brewery. By quantitative accounting, the study was able to decipher trends that indicate the impact of EMS to the input use of the brewery. However, statistically the model yielded no valid justification that EMS indeed had significant impact in the given five years. Henceforth, along the analysis, the model may have indicated impact of EMS, but statistically, the model used was not able to exhibit concrete and significant impact of EMS on the input use of the brewery.